The realization of the right to freedom of speech on the Internet - I. S. Fliter (Цифровое право, 2021)
The expression of opinions on the Internet has a number of features in comparison with traditional means of information dissemination. Firstly, imposition of classical measures of legal liability can be difficult due to the peculiarities of cyber space: anonymity and erasure of jurisdictional boundaries. In this regard, a new mechanism of restrictions has appeared, which consists in the withdrawal of information that violates the law or the rights of other citizens from the Internet at the direction of state bodies. The trends in this area are the predominance of the administrative procedure for making decisions on the withdrawal of information from public access, and the use of vague and evaluative terms as grounds for restrictions. Secondly, in most cases, in the process of realizing freedom of speech, intermediaries are involved — companies that provide a public forum for millions of users. The activities of these companies are also associated with new mechanisms for restricting freedom of speech: from blocking content to deleting users’ accounts. Such companies have a dual responsibility: to monitor the placement of content in order to prevent abuse of freedom of speech and to prevent violations of freedom of expression with their own corporate rules. The purpose of this article is to identify, through the method of analytical jurisprudence, the problems that arise when restricting freedom of speech, implemented in the digital environment, and to establish the reasons for their occurrence. To do this, the author has carried out a review of Russian legislation and the practice of its application, as well as the practice of restrictions, applied by corporations, and an analysis of foreign literature.